The Insertion of Latin America in the Global Context. A Focused Approach to Regional Economic Development - Silva, Luiz César Fernandes da; Mourão, Paulo Reis (European Journal of Multidisciplinary Studies, 2018)
The 90's was a period of significant change for the Latin American economies. Countries experience considerable political and institutional reforms to make the trade and financial openness. The implemented model of economic development shall be based on liberalizing measures in reducing the state's role in the economy and was attributed to the market the lead role of inducing economic system. At the end of the decade, poor results on the economic and social sphere were reflected in several countries and a further review in development policies is now favored. Thus, the ideas of theoretical analysis of the thinking of the Economic Studies Committee to Latin - America (CEPAL) is postulated on the agenda. Based on the Keynesian thought and a historical-structural approach, the production of the institution lies in the analysis of the conjecture and consequences of deregulation and economic and financial liberalization that prevailed. He proposed an approach to regional economic development that would reconcile economic growth with better income distribution, employment and growth with technical progress and social equity. This paper considers, by inserting the Latin American countries in the global integration in the 90s, the ideal of theoretical analysis of the thinking of CEPAL, the socioeconomic situation, as an alternative form of the reforms made in that decade. Therefore, it makes for a bibliographic approach, a reflective analysis highlighting the opinion of the institution.
Keywords: CEPAL; Development; Productive processing; Social Equity